2003
DOI: 10.2135/cropsci2003.0037
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Improvement of Agronomic Traits of Winter Wheat Cultivars Released in France from 1946 to 1992

Abstract: usually provides more directly comparable information, particularly about yield components. The main results In a context where agricultural practices in Europe are likely to of such studies are given in Table 1. Genetic gains for go toward extensive systems with lower inputs, it is important to determine the genetic improvement of winter wheat (Triticum aesti-grain yield varied from 5.8 kg ha Ϫ1 yr Ϫ1 to 59 kg ha Ϫ1 vum L.) not only in high-input agricultural systems but also in low-yr Ϫ1 . Theses gains repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
121
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 0 publications
16
121
0
7
Order By: Relevance
“…Harvest index improvements were positively associated with plant height reductions, as has been pointed out in other species (Calderini et al 1995;Brancourt-Hulmel et al 2003). Future improvements in grain yield through breeding may require a boost in biomass production, with harvest index being maintained (Austin et al 1980;Hay 1995;Fischer 1996) or further increases in harvest index.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Harvest index improvements were positively associated with plant height reductions, as has been pointed out in other species (Calderini et al 1995;Brancourt-Hulmel et al 2003). Future improvements in grain yield through breeding may require a boost in biomass production, with harvest index being maintained (Austin et al 1980;Hay 1995;Fischer 1996) or further increases in harvest index.…”
Section: Discussionmentioning
confidence: 53%
“…The higher number of grains per unit area has been the yield component most associated with yield gains in bread wheat (McCaig and Clarke 1995) and barley (Jedel and Helm 1994). Nevertheless, changes in grain weight have been null (McCaig and Clarke 1995) or even negative (Perry and D'Antuono 1989;Brancourt-Hulmel et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Overwhelmingly, in the Spark · Rialto cross, yield QTL across all environments also relate to variation in grain size, much more so than any other trait. This is encouraging since there has previously apparently been little change in grain size with wheat breeding in recent decades world-wide (eg., Calderini et al 1999;Brancourt-Hulmel et al 2003;Shearman et al 2005). In fact, there are other significant QTL relating to grain size which are present but whose co-locating yield QTL do not reach statistical significance.…”
Section: Genetic Analysis Of Yield Sink Traitsmentioning
confidence: 98%
“…Genetic improvements have made substantial contributions to wheat yield increases in countries such as Britain (Austin et al 1980(Austin et al , 1989, France (Brancourt-Hulmel et al 2003), Italy (Canevara et al 1994), United States (Cox et al 1988;Donmez et al 2001), Canada (Hucl and Baker 1987;McCaig and DePauw 1995), Australia (Perry and D'Antuono 1989), Argentina (Slafer and Andrade 1989;Calderini et al 1995), Mexico (Waddington et al 1986;Sayre et al 1997;OrtizMonasterio et al 1997) and India (Kulshrestha and Jain 1982). Most of these studies showed that grain yield increases are mainly associated with increased harvest index (HI) resulting from reduced plant height, and increased kernel numbers/m 2 .…”
Section: Introductionmentioning
confidence: 99%